Recombinant Protein Containing B-Cell Epitopes of Different Loxosceles Spider Toxins Generates Neutralizing Antibodies in Immunized Rabbits - Lima, Sabrina de Almeida; Guerra-Duarte, Clara; Costal-Oliveira, Fernanda; Mendes, Thais Melo; Figueiredo, Luís F. M.; Oliveira, Daysiane; Machado de Avila, Ricardo A.; Ferrer, Valéria Pereira; Trevisan-Silva, Dilza; Veiga, Silvio S.; Minozzo, João C.; Kalapothakis, Evanguedes; et al. (Frontiers in Immunology, 2018)
Loxoscelism is the most important form of araneism in South America. The treatment of these accidents uses heterologous antivenoms obtained from immunization of production animals with crude loxoscelic venom. Due to the scarcity of this immunogen, new alternatives for its substitution in antivenom production are of medical interest. In the present work, three linear epitopes for loxoscelic astacin-like metalloprotease 1 (LALP1) (SLGRGCTDFGTILHE, ENNTRTIGPFDYDSIMLYGAY and KLYKCPPVNPYPGGIRPYVNV) and two for hyaluronidase (LiHYAL) (NGGIPQLGDLKAHLEKSAVDI and ILDKSATGLRIIDWEAWR) from Loxosceles intermedia spider venom were identified by SPOT-synthesis technique. One formerly characterized linear epitope (DFSGPYLPSLPTLDA) of sphingomyelinase D SMase-I from L. laeta was also chosen to constitute a new recombinant multiepitopic protein. These epitopes were combined with a previously produced chimeric multiepitopic protein (rCpLi) composed by linear and conformational B-cell epitopes from sphingomyelinase-D (SMase D) from L. intermedia venom, generating a new recombinant multiepitopic protein derived from loxoscelic toxins (rMEPLox). We demonstrated that rMEPLox is non-toxic and antibodies elicited in rabbits against this antigen present reactivity in ELISA and immunoblot assays with Brazilian L. intermedia, L. laeta, L. gaucho and L. similis spider venoms. In vivo and in vitro neutralization assays showed that anti-rMEPLox antibodies can efficiently neutralize the sphingomyelinase, hyaluronidase and metalloproteinase activity of L. intermedia venom. This study suggests that this multiepitopic protein can be a suitable candidate for experimental vaccination approaches or for antivenom production against Loxosceles spp venoms.